Stress and lifestyle of the adult youths in Bydgoszcz - Kostencka, Alicja; Sławiński, Szymon; Dziembowska, Inga (Journal of Education, Health and Sport, 2017)
Nowadays, we observe an increase of stress and unhealthy behaviours in the youth. Health behaviours are the basic components of life style and may affect not only physical health but also other dimensions of health, including mental health, which is a growing health problem for young people. The purpose of this study was to evaluate the connection between stress level that affects the youth before secondary school graduation exam with selected health behaviours. The youth that are now several months before secondary school graduate exam are characterized by a moderate level of stress. Some of the health behaviours are conditioned upon the stress level of secondary school graduates. This applies to smoking marijuana and number of hours spend in front of the screen of computer, TV and other similar devices. Lifestyle can be affected by stress level but also by many other factors. This suggests the need of applying qualitative research, which may contribute to implementing effective prevention of negative health behaviours.